2017
DOI: 10.1080/13880209.2017.1312464
|View full text |Cite
|
Sign up to set email alerts
|

Development of essential oils as skin permeation enhancers: penetration enhancement effect and mechanism of action

Abstract: Compared with azone, the investigated EOs possess significantly higher penetration enhancement effect and lower skin toxicity. EOs can promote the skin permeation of ibuprofen mainly by disturbing rather than extracting the SC lipids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 33 publications
2
54
0
1
Order By: Relevance
“…When compared with azone, the tested EOs had significantly higher penetration enhancement effect and lower skin irritation potential. The results revealed that EOs can enhance the skin permeation of ibuprofen mainly by disturbing the stratum corneum lipids [ 54 ].…”
Section: Biological Activities Of Angelica Essementioning
confidence: 99%
“…When compared with azone, the tested EOs had significantly higher penetration enhancement effect and lower skin irritation potential. The results revealed that EOs can enhance the skin permeation of ibuprofen mainly by disturbing the stratum corneum lipids [ 54 ].…”
Section: Biological Activities Of Angelica Essementioning
confidence: 99%
“…Whereas formulation A2 showed an optimum release of 77% at the end of the experiment, which is evident as per studies conducted by Jiang that essential oils such as terpenes which are generally regarded as safe (GRAS) being hydrophobic in nature take a bit longer t to interact with the buffer medium and drug dissolution thus, a sustained effect is obtained and by altering the concentration of the oil the release of the drug can be regulated. (Jiang et al 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Similar studies were conducted by Jiang et al, where different permeation enhancers were used and concluded that essential oils are safe, non-toxic and an effective way of delivering many drugs across skin by causing a reversible change in the stratum corneum. (Jiang et al 2017 ).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Some studies suggest that hydrocarbon terpenes like limonene (log p value of 4.53) are more effective to enhance skin penetration of lipophilic drugs like PGZ (log p value of 2.3) [ 45 , 46 ]. Terpenes consist of isoprene units that enhance the permeation of hydrophilic and lipophilic drugs [ 47 ]. The mechanism of action of limonene as a penetration enhancer is based on changing the structure of lipids between the stratum corneum, with a consequent increase of intercellular diffusivity and improvement of drug partitioning into the tissue [ 48 ].…”
Section: Discussionmentioning
confidence: 99%